Weighted Word Pairs for query expansion. Issue 1 (January 2015) - Colace, Francesco; De Santo, Massimo; Greco, Luca; Napoletano, Paolo
Highlights A graph of terms can be effectively used for query expansion. Such a graph is extracted from documents thanks to a LDA based methodology. Proposed method achieves good performances on standard datasets.